Bacterial Assay of Drinking Water Commercially Marketed in Bharatpur Metropolitan City, Chitwan, Nepal - Khanal, Bipin; Pokhrel, Galaxy; Khanal, Ranjana; Bhattarai, Bodh Babu; Pokhrel, Ganga Raj (BMC Journal of Scientific Research, 2024)
The bacterial assay of Drinking Water Commercially Marketed in Bharatpur Metropolitan City, Chitwan, Nepal is still not understood clearly. Out of twenty samples, ten samples were collected from 1 L bottles and ten samples were collected from 20 L water jars. The pH of the sample solution was evaluated using pH meter (AUTO DEULEX METERMODEL; LT-10). The most probable number (MPN) method was used to analyze Salmonella, yeast, and Mould while the membrane filtration technique was used to evaluate coliforms and fecal coliforms. Yeast and mold were cultured in Sabouraud Dextrose Broth while M-Lauryl Sulphate Broth solution was used for total coliform and fecal coliform. Salmonella was cultured in Rappaport Vassiliadis Salmonella Enrichment Broth media. The pH of most of samples lies between 6.5–8.5 which is very close to the National Drinking Water Quality standard, Nepal and WHO while some samples ranges below the National Drinking Water Quality Standard, Nepal. There is no any growth of the Fecal coliform bacteria in all the samples of one 1 L bottles whereas 50% of the samples of 1 L water bottle showed the abundance of total coliform. The result revealed that the 20 L jar water was contaminated with total and faecal coliform bacteria. Out of the ten samples of one 1 L water bottle, nine samples were contaminated with total coliform whereas samples from 20 L jar showed 70% contamination with fecal coliform. Neither of the samples spotted Salmonella, mould and yeast. This study reveals the importance of monitoring the quality of drinking water production system.